DISCOVERING THE PERFORMANCES OF HYBRIDITY AND POST-COLONIALISM IN THE ANSWER OF DE LA CRUZ’S THROUGH A BHABHIAN DETAILED ANALYSIS OF THE CRISIS OF CULTURAL IDENTITY (American Journal of Research in Humanities and Social Sciences, 2024)
This study investigates the performance of identity and culture in postcolonial literature, emphasizing how these authors engage in a strong critique and opposition to the colonial past. Drawing on Said's Orientalist theories as well as Bhabha's (1994) ideas of mimesis and hybridity, this dissertation seeks to identify one way in which postcolonial literature reflects the complexity of identity creation within colonially dominated countries. According to the article, postcolonial literature does more than just criticize the cultural and psychological repercussions of colonialism; it also reconfigures identity and builds elements of resistance. Indeed, postcolonial literature offers fresh insights into the lingering effects of colonial legacies on contemporary society by redefining global conceptions of identity, culture, and power in a postcolonial world. It is clear from an analytical perspective.